Finite‐time H ∞ control for discrete‐time switched nonlinear systems with time delay. (2nd December 2013) - Zong, Guangdeng; Wang, Ruihua; Zheng, Weixing; Hou, Linlin
Summary In this paper, the problem of finite‐time H ∞ control is addressed for a class of discrete‐time switched nonlinear systems with time delay. The concept of H ∞ finite‐time boundedness is first introduced for discrete‐time switched delay systems. Next, a set of switching signals are designed by using the average dwell time approach, under which some delay‐dependent sufficient conditions are derived to guarantee the H ∞ finite‐time boundedness of the closed‐loop system. Then, a finite‐time H ∞ state feedback controller is also designed by solving such conditions. Furthermore, the problem of uniform finite‐time H ∞ stabilization is also resolved. All the conditions are cast into linear matrix inequalities, which can be easily checked by using recently developed algorithms for solving linear matrix inequalities. A numerical example and a water‐quality control system are provided to demonstrate the effectiveness of the main results. Copyright © 2013 John Wiley & Sons, Ltd.